Bioengineered 3D ovarian model for long-term multiple development of preantral follicle: bridging the gap for poly(ε-caprolactone) (PCL)-based scaffold reproductive applications - Di Berardino, Chiara; Peserico, Alessia; Camerano Spelta Rapini, Chiara; Liverani, Liliana; Capacchietti, Giulia; Russo, Valentina; Berardinelli, Paolo; Ünalan, Irem; Damian-Buda, Andrada-Ioana; Boccaccini, Aldo R.; Barboni, Barbara (Reproductive Biology and Endocrinology, 2024)
Background: Assisted Reproductive Technologies (ARTs) have been validated in human and animal to solve reproductive problems such as infertility, aging, genetic selection/amplification and diseases. The persistent gap in ART biomedical applications lies in recapitulating the early stage of ovarian folliculogenesis, thus providing protocols to drive the large reserve of immature follicles towards the gonadotropin-dependent phase. Tissue engineering is becoming a concrete solution to potentially recapitulate ovarian structure, mostly relying on the use of autologous early follicles on natural or synthetic scaffolds. Based on these premises, the present study has been designed to validate the use of the ovarian bioinspired patterned electrospun fibrous scaffolds fabricated with poly(ε-caprolactone) (PCL) for multiple preantral (PA) follicle development. Methods: PA follicles isolated from lamb ovaries were cultured on PCL scaffold adopting a validated single-follicle protocol (Ctrl) or simulating a multiple-follicle condition by reproducing an artificial ovary engrafted with 5 or 10 PA (AO5PA and AO10PA). The incubations were protracted for 14 and 18 days before assessing scaffold-based microenvironment suitability to assist in vitro folliculogenesis (ivF) and oogenesis at morphological and functional level. Results: The ivF outcomes demonstrated that PCL-scaffolds generate an appropriate biomimetic ovarian microenvironment supporting the transition of multiple PA follicles towards early antral (EA) stage by supporting follicle growth and steroidogenic activation. PCL-multiple bioengineering ivF (AO10PA) performed in long term generated, in addition, the greatest percentage of highly specialized gametes by enhancing meiotic competence, large chromatin remodeling and parthenogenetic developmental competence. Conclusions: The study showcased the proof of concept for a next-generation ART use of PCL-patterned scaffold aimed to generate transplantable artificial ovary engrafted with autologous early-stage follicles or to advance ivF technologies holding a 3D bioinspired matrix promoting a physiological long-term multiple PA follicle protocol.
CRIS-Team Scopus Importer:2024-08-16
Keywords: in vitro folliculogenesis; in vitro oogenesis; Tissue engineering; Artificial-ovary; Preantral follicle development; Large chromatin remodeling; Oocyte maturation; Parthenogenetic activation; Embryo development; PCL-electrospun scaffold